The Role of Islamic Religious Education in Promoting Tolerance and Interfaith Dialogue - Santosa, Tomi Apra; Wahyudi, Muhammad; Wijoyo, Hadion; Kurniawan, Andri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research aims to analyze the role of Islamic religious education in fostering tolerance and encouraging dialogue between religious communities in a multicultural society. Using a qualitative approach to literature, this study examines various literature, curricula, and learning practices that are oriented towards the values of religious moderation (wasathiyyah) and respect for diversity. The results of the study show that Islamic religious education not only functions as a means of transmitting teachings, but also as a medium for internalizing Islamic universal values that uphold justice, peace, and human brotherhood. Through the application of dialogical, collaborative, and contextual learning strategies, Islamic religious education can strengthen students' critical awareness, prevent the emergence of intolerance, and build interfaith communication skills. Thus, Islamic religious education plays a significant role in creating a generation that is religious and inclusive, able to maintain its religious identity without negating the existence of other religions.